We are given 3 equations. Using these equations we can find f(h(2)).
h(x)=7x-5
h(2)=7(2)-5
h(2)=14-5
h(2)=9
f(x)=x^2-7
f(h(2))=(7x-5)^2-7
we know the answer for h(2) by now, so we can substitute for that.
f(9)=9^2-7
f(9)=81-7
f(9)=74
so f(h(2))=74
Answer:
21
Step-by-step explanation:
1/3= 0.33
7/0.33
Hello :
the general term is :
an = a1+(n-1)×d
or : an = ap +(n-p)×d......d is common diffrence
let : n=10 and p= 4
a10 = a4 +(10-4)×d
64 = 22 + 6d
6d = 42
d= 7
conclusion :
a4 = 22
a3 = 22-7=15
a2=15-7=8
a1= 8-7=1
<span>the first five terms : 1 , 8 , 15 , 22</span>
Answer: £2520
Step-by-step explanation:
You have $4000 to convert to British pounds (?). 4,000*.63=2,520.